Menstrual Fluid Factors Mediate Endometrial Repair - Salamonsen, Lois A. (Frontiers in Reproductive Health, 2021)
Menstruation is a process whereby the outer functionalis layer of the endometrium is shed each month in response to falling progesterone and estrogen levels in a non-conception cycle. Simultaneously with the tissue breakdown, the surface is re-epithelialized, protecting the wound from infection. Once menstruation is complete and estrogen levels start to rise, regeneration progresses throughout the proliferative phase of the cycle, to fully restore endometrial thickness. Endometrial repair is unique compared to tissue repair elsewhere in the adult, in that it is rapid, scar-free and occurs around 400 times during each modern woman’s reproductive life. The shedding tissue and that undergoing repair is bathed in menstrual fluid, which contains live cells, cellular debris, fragments of extracellular matrix, activated leukocytes and their products, soluble cellular components and extracellular vesicles. Proteomic and other analyses have revealed some detail of these components. Menstrual fluid, along with a number of individual proteins enhances epithelial cell migration to cover the wound in endometrial epithelial and keratinocyte cell culture models, in an ex vivo decellularized skin model and in pig wounds in vivo. Thus, the microenvironment provided by menstrual fluid, is likely responsible for the unique rapid and scar-free repair of this remarkable tissue. Insight gained from analysis of this fluid is likely to be of value not only for treating endometrial bleeding problems but also in providing potential new therapies for poorly repairing wounds such as those seen in the aged and in diabetics.